Enantioselective separation of ofloxacin by ligand exchange chromatography - Dat, Nguyen Tien; Vuong, Nguyen Quoc; Hong Hanh, Tran Thi (Vietnam Journal of Chemistry, 2015)
A ligand exchange HPLC method for enantioseparation of ofloxacin enantiomers was developed by a using C8 stationary phase. Chromatographic separation was performed on a Zorbax-300SB-C8 column eluted with the mobile phase consisting of 15 % methanol in water containing 10mM phenylalanin and 5 mM CuSO4 at flow rate of 0.8 mL/min. The method was simple, rapid and suitable for routine analytical studies of ofloxacin enantiomers.